2018
DOI: 10.1186/s12889-018-5942-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of life using WHOQOL-BREF: a cross-sectional study on the association between quality of life and neighborhood environmental satisfaction, and the mediating effect of health-related behaviors

Abstract: BackgroundQuality of life (QOL) is an important component in assessing people’s health. Environmental quality can influence people’s QOL in the physical health, psychological, social relationships and environment domains. QOL in the four domains, overall QOL and general heath of residents living in the Kowloon Peninsula of Hong Kong were assessed. The association between satisfaction with the neighborhood environment and QOL, and health-related behaviors which mediated the effect were investigated.MethodsA sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(114 citation statements)
references
References 42 publications
11
94
1
8
Order By: Relevance
“…The findings suggest that it positively affects physical activity and physical QoL, even if the space is limited, which is a characteristic of the urban area of Hong Kong. Previous studies suggest green space had a positive effect not only on physical health and activity [19,24,41,59] but also on psychological health [22,31,60]. In our study, there were significant benefits of green space on physical activity and physical health but not on psychological health.…”
Section: [Figure 3]supporting
confidence: 45%
See 2 more Smart Citations
“…The findings suggest that it positively affects physical activity and physical QoL, even if the space is limited, which is a characteristic of the urban area of Hong Kong. Previous studies suggest green space had a positive effect not only on physical health and activity [19,24,41,59] but also on psychological health [22,31,60]. In our study, there were significant benefits of green space on physical activity and physical health but not on psychological health.…”
Section: [Figure 3]supporting
confidence: 45%
“…Perception of the public open space and built environment are essential constituent in the evaluation of the neighbourhood, health [36] and QoL [37]. Our earlier study, however, found that satisfaction with the neighbourhood environment was only significantly related to psychological QoL [31]. Residents who reported perceived moderate satisfaction with the public space in neighbourhood had significantly higher psychological QoL.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Still, the connections between soundscape as a perceptual construct [17] and health effects are under investigated [18]. Quality of 2 of 27 urban open spaces is an indicator for quality of city life [19], yet urban spaces are generally highly exposed to urban noise sources, i.e., the streets often being the very source of motor traffic noise, which is also the source which has the highest impact on population's health [20,21]. On the other side, lowering sound pressure levels were proved to be insufficiently effective for achieving acoustic comfort [22].…”
Section: Introductionmentioning
confidence: 99%
“…Przegląd międzynarodowej literatury dotyczącej jakości życia pokazuje jednak, że w zależności od specyficznych warunków w poszczególnych krajach wyniki mogą się różnić. Na przykład z badań przeprowadzonych w Hongkongu wynika, że tamtejsi mieszkańcy mają niższe poczucie jakości życia w dziedzinie zdrowia fizycznego i psychicznego, ale podobne w dziedzinie stosunków społecznych i środowiska w porównaniu z innymi krajami [13].…”
Section: Dyskusjaunclassified